MARCH8 inhibits HIV-1 infection by reducing virion incorporation of envelope glycoproteins - Tada, Takuya; Zhang, Yanzhao; Koyama, Takayoshi; Tobiume, Minoru; Tsunetsugu-Yokota, Yasuko; Yamaoka, Shoji; Fujita, Hideaki; Tokunaga, Kenzo (Nature medicine, 2015)
Kenzo Tokunaga and colleagues report that MARCH8 inhibits the incorporation of the HIV-1 envelope glycoprotein into virus particles, thereby reducing viral infectivity. Membrane-associated RING-CH 8 (MARCH8) is one of 11 members of the recently discovered MARCH family of RING (really interesting new gene)-finger E3 ubiquitin ligases 1 , 2 . MARCH8 downregulates several host transmembrane proteins, including major histocompatibility complex (MHC)-II, CD86, interleukin (IL)-1 receptor accessory protein, TNF-related apoptosis-inducing ligand (TRAIL) receptor 1 and the transferrin receptor 3 , 4 , 5 , 6 , 7 . However, its physiological roles remain largely unknown. Here we identify MARCH8 as a novel antiviral factor. The ectopic expression of MARCH8 in virus-producing cells does not affect levels of lentivirus production, but it does markedly reduce viral infectivity. MARCH8 blocks the incorporation of HIV-1 envelope glycoprotein into virus particles by downregulating it from the cell surface, probably through their interaction, resulting in a substantial reduction in the efficiency of viral entry. The inhibitory effect of MARCH8 on vesicular stomatitis virus G-glycoprotein is even more remarkable, suggesting a broad-spectrum inhibition of enveloped viruses by MARCH8. Notably, the endogenous expression of MARCH8 is high in monocyte-derived macrophages and dendritic cells, and MARCH8 knockdown or knockout in macrophages significantly increases the infectivity of virions produced by these cells. Our findings thus indicate that MARCH8 is highly expressed in terminally differentiated myeloid cells, and that it is a potent antiviral protein that targets viral envelope glycoproteins and reduces their incorporation into virions.